Focal cortical dysplasia type 1 - Coras, Roland; Holthausen, Hans; Sarnat, Harvey B. (Brain Pathology, 2021)
The ILAE classification of Focal Cortical Dysplasia (FCD) from 2011 has quickly gained acceptance in clinical practice and research and is now widely used around the world. This histopathology-based classification scheme proposed three subtypes, that is, FCD Type 1 (with architectural abnormalities of the neocortex), FCD Type 2 (with cytoarchitectural abnormalities of the neocortex) and FCD Type 3 (architectural abnormalities of the neocortex associated with another principle lesion acquired during early life). Valuable knowledge was gathered during the last decade validating the clinical, pathological and genetic classification of FCD Type 2. This is in contrast to FCD subtype 1 and 3 with only few robust or new insights. Herein, we provide an overview about current knowledge about FCD Type 1 and its three subtypes. Available data strengthened, however, FCD Type 1A in particular, whereas a comprehensive clinico-pathological specification for FCD Type 1B and 1C subtypes remain to be shown. The lack of a valid animal model for FCD Type 1 further supports our call and the ongoing need for systematic research studies based on a careful clinico-pathological and genetic stratification of patients and human brain tissues.
CRIS-Team Scopus Importer:2021-07-16
Keywords: focal cortical dysplasia type 1